Implementation of a Fraud Control Plan in the Management of School Operational Assistance Funds - Antoni, Jono; Candira, Dedi; Hamengkubuwono; Istan, Muhammad (El-Idare: Journal of Islamic Education Management, 2024)
This study examines the implementation of the Fraud Control Plan (FCP) in managing School Operational Assistance (BOS) funds at SD Negeri 12 Kepahiang. The primary issues identified include low transparency and accountability in fund management and indications of fund misuse due to limited oversight. The research employs a qualitative method with a descriptive approach through interviews, observations, and document analysis. The findings reveal that FCP implementation begins with the formulation of internal policies as a guide for fund management, followed by the establishment of structured management procedures, internal monitoring, and training for relevant parties. Technology is also utilized to enhance transparency in fund usage. Risk identification in BOS fund management highlights potential misuse during the planning, implementation, and reporting stages, necessitating strict oversight. Fraud prevention and detection strategies include robust internal controls, the use of technology, and external supervision by the school committee and the education department. However, FCP implementation faces challenges such as limited human resources and technology, as well as resistance to change. Supporting factors that strengthen FCP implementation include an effective internal monitoring system and good understanding of accountability, while the main obstacles are the low administrative staff awareness and limited technological infrastructure. The study recommends further training and technological capacity-building to ensure the sustainable and effective application of FCP.